Definisi Integrasi Layanan Kesehatan Primer: Perspektif dari Pimpinan Puskesmas - Andy Amimr; Puspita Sari; Herwansyah (Jurnal Kesehatan, 2024)
Integrating primary health services is crucial for improving the quality and accessibility of healthcare at the community level. This qualitative study investigates how leaders of Puskesmas define and implement integration within their services, as well as the challenges and factors that influence this process. Ten Puskesmas leaders in several Municipalities of the Province of Jambi and one key informant from the Municipal Department of Health were interviewed to obtain in-depth insights. Data collection was conducted through semi-structured interviews, and the information was analyzed using content analysis methods. The findings indicate that integration is viewed as a multi-dimensional strategy to enhance patient care coordination, maximize resource efficiency, and improve community health outcomes. Key factors affecting integration include leadership styles, inter-departmental collaboration, and the support provided by municipal health authorities. This study underscores the importance of robust leadership and strategic partnerships in facilitating service integration at the primary health center level, providing valuable insights for policymakers and healthcare administrators.